Hambatan Dan Kendala Dalam Pelaksanaan Pembelajaran Daring Pasca Covid-19 - Ni Made Arini; Ida Bagus Alit Arta Wiguna (Cetta: Jurnal Ilmu Pendidikan, 2021)
The pandemic Covid-19 has made major changes in almost all aspects of human life, one of which is the education system. Changes in the education system are forced to make it difficult for students to take courageous learning and accept learning materials, especially students at an early age, because learning that is usually done conventionally becomes learning that is free to change, with its implementation inseparable from the role of teachers and technology. This research aims to examine the obstacles and obstacles faced by teachers in carrying out bold learning after Covid-19. The method in this study uses a qualitative method with exploratory characteristics. The results and conclusions in this paper indicate that the obstacles and obstacles when learning courage is that the teacher is not used to it and does not have interesting learning materials to carry out bold learning. The obstacle is the limited information and government, regarding the provision of assistance for school health service facilities.